(untitled) (UNWE Yearbook, 2015)
The subject of this study are the main economic aspects of disasters and cataclysms of nature, in particular the essence of the economic policy that has to limit (prevent and mitigate) their implications. The study employs as information sources the author’s available and accessible data on the topic as well as the practice of the European Commission in response to natural disasters.The study highlights: a) causes, trends, size and frequency of disasters (caused by man and nature); b) the economic implications thereof and the ability (including priorities) to prevent damage - principles, legislative and practice-oriented decisions based on European Union’s policy to disaster risk management, both within the EU and in support of the developing countries.The author claims that the art of survival in an era of disasters imposes imperative embedding of sustainability measures against the associated risks, with no other alternatives at present.